A Critical Review of Authentic Assessment Principles in the Context of Islamic Religious Education Learning - Darun Mutammimah; Ika Fisyatil Kamila; Dina Kamilia; Juhairiyah Juhairiyah; Eliyatul Fitriyah (Penerbit Presisi Pustaka, 2026)
Authentic assessment has great potential to measure students’ holistic competencies, going beyond the limits of traditional cognitive tests. In Islamic Religious Education (PAI), which emphasizes character formation and value internalization, the application of authentic assessment is essential to ensure that evaluation aligns with the spiritual goals of education. This study aims to examine the fundamental principles of authentic assessment, analyze their relevance to PAI evaluation, and formulate necessary modifications to enhance validity and reliability in the spiritual and affective domains. A comparative literature review method was employed, drawing from classical authentic assessment theories and the philosophy of Islamic educational evaluation. The findings indicate that the principles of contextuality and performance focus are highly relevant, while objectivity poses methodological challenges in assessing sincerity and moral character. The proposed solution involves applying spiritual data triangulation and continuous assessment. The study concludes that authentic assessment in PAI requires fundamental adaptation to maintain ecological validity without compromising assessment integrity.